What Do Single-Fiber Studies Tell Us about Exercise Training? - Malisoux, L.; Francaux, M.; Theisen, D. (Medicine & Science in Sports & Exercise, 2007)
Many exercise programs designed by trainers have the specific aim to enhance strength, endurance, or power of certain muscle groups to improve athletic performance. Muscle training is also an important component of rehabilitation to limit atrophy associated with immobilization, aging, or disease. To optimize exercise interventions, a good understanding of the response to various training programs and the identification of the mechanisms that influence muscle function are required. Changes in the performance of muscle contraction are associated, among other things, with muscle fiber-type expression and functional properties of the contractile apparatus. Chemically skinned, single fibers is the only model that allows study of the mechanical properties of human muscle fibers as a function of the expression of myosin heavy-chain isoforms. Recently, this model has been used to explore the functional adaptations after different types of solicitations. The current results of the literature indicate that cross-sectional area and force of a specific fiber type are enhanced after resistance training, whereas maximal unloaded shortening velocity is increased by endurance training. Plyometric training improves both fiber force and shortening velocity. Fiber peak power is increased after resistance or plyometric training, and on a long-term basis it is decreased after endurance training. Studies on elderly individuals indicate that this population may react differently with respect to some single-fiber adaptations after training. Generally, training regimens tend to decrease the proportion of type IIx fibers. The available data in the literature make it possible to formulate recommendations applicable to sport science and rehabilitation.